Ecologia de peixes que ocupam diferentes habitats da Planícies de inundação do rio Mogi-Guaçu, SP - Simabuku, Mara Adriana Marçal (2005)
Fish from the Mogi-Guaçu River floodplains were sampled mostly in the wet season of 2001 to 2004, using several sampling gears, such as gill nets, sieves and a Dip net. Sixty two species were collected, belonging to 5 orders and 23 families; Capture for Unit Efford (CPUE) data indicated the predominance of lentic species of small characids in all habitats, except in the temporary flooded areas where early juvenil and juveniles of facultative migratory species prevailed; in lower proportion juveniles and adults of migratory species occurred in oxbow lakes and backwaters, early juvenil in tributaries and larvae, early juvenil, and juveniles in flooded areas. Dissolved oxygen concentrations were low in small temporary pools and temporary flooded areas, varying in the oxbow lakes. The relative abundance of standard length classes of some species such as Prochilodus lineatus and three species of Astyanax evidenced the preference of lower population strata for temporary flooded areas of upper Mogi-Guaçu, whereas higher strata occurred in oxbow lakes; backwaters and tributaries are inhabited by all population strata in low abundance. Eggs, in high densities, were sampled by ichthyoplankton net and Dip net only in the main river and its backwaters downstream Cachoeira de Emas dam, in the medium-upper stretch of Mogi-Guaçu River, in January 2003 and 2004. Evaluation of the anthropic influence on the watershed, revealed that deepening of the river channel by sand excavation, drainage of floodplains and river flow control by hydroelectric dams are changing flood patterns, as well as pollution by domestic sewage is negatively influencing fish nurseries.